Religious Intolerance and Cinematic Representations: A Study of Selected Short-Films on the 1984 anti- Sikh Pogrom in India - Ishmeet Kaur Chaudhry (Universitat Autònoma de Barcelona, 2017)
This paper explores the theme of fragmentation and focuses specifically on the Sikh massacres of 1984 which followed the assassination of the Indian Prime Minister Indira Gandhi when she was gunned down by her Sikh body guards. Thirty two years down the line no perpetrators of the mob attacks and mass killings of the Sikhs have been brought to justice. The Indian sub-continent enfolds, within what appears to be the borders of a single nation, a bewildering complex of racial religious, social and cultural identities and any attempt to over-simplify the forces of division and conflict runs the risk of gross misrepresentation. More recently, the deliberated muting of the issues of justice against the Sikhs are apparent in the banning of the two latest films on the subject.  In the present paper three short films have been analysed: “Injustice 1984,” directed by Jarnail Singh; “Jagjeet” (2010), directed by Kavanjit Singh and “Kush” (2013), directed by Subhashish Bhutiani. These films depict real-life stories of persons from the Sikh community and explore the impact of religious intolerance and the violence of the Sikh massacres from the perspective of the victims. It seeks to highlight concerns regarding religious intolerance, questions of identity, legal silences and deliberated muting of the subject over the past years and the need for a complex critical evaluation of the responsibility of the state and its socio-institutional bodies towards its citizens.